Syria as an Arena of Strategic Competition - Martini, Jeffrey (RAND Corporation, 2013)
Less than two years since the beginning of the uprising in Syria, localized protests have morphed into full-blown civil conflict, and external actors have become involved as well. RAND conducted an analytic exercise to generate a greater understanding of the parties and issues in play, including the actors, their motivations, and potential impact of their activities.